Controversies in Early Liver Transplantation for Severe Alcoholic Hepatitis - Tiffany Wu (Annals of Hepatology, 2018)
Alcoholic hepatitis (AH) is a condition of acute liver inflammation in the setting of heavy alcohol use that is often managed with corticosteroids in severe cases. Among non-responders to steroids, however, prognosis is poor with up to 75% mortality within 6 months after treatment failure. Early liver transplantation (LT) can achieve an acceptable short-term survival, and initial studies have demonstrated 3-year survival rates of up to 84%. However, the practice of early LT in severe AH remains controversial with concerns over the 6-month rule of sobriety and risk of alcohol relapse post-transplant. Proponents of LT advocate for better understanding of alcohol use as a disorder rather than self-inflicted cause of illness, aim to redefine the misguided application of the 6-month rule, and point out similar relapse rates among patients with early LT and those with greater than 6 months abstinence before transplant. Opponents of LT emphasize the correlation between alcohol relapse and graft failure and mortality, public resistance and potential for distrust among donors, and arguments that transplant centers need to establish improved models to predict relapse and standardize candidate selection criteria across centers. Here we review recent literature on this controversy and provide recommendations for moving forward to consensus.